Intra-pulse modulation recognition of radar signal based on random forest - Ge LIU; Guoyi ZHANG; Yan YU (Dianxin kexue)
To solve the existing problems of low recognition rate and noise problem in radar signal recognition,the fusion feature extraction method of time-frequency image and the random forest classifier is applied to the identification of radar signals.The radar signal time-frequency image was firstly extracted the shape features and texture features to anstitute fusion characteristics,into and then input fusioncharacteristics radom forest classifier recognition of the signal classification was realized.The results of simulation experiments for eight kinds of common radar signals to recognition show that recognition accuracy of the method proposed can be achieved more than 90% in SNR -2 dB,so it also verify the effectiveness of the method.